Роль чинників росту у розвитку доброякісної гіперплазії передміхурової залози та їх зв’язок із метаболічним синдромом - Кирилюк, М. Л.; Костєв, Ф. І.; Підаєв, А. В.; Шаталюк, С. С. (Clinical Endocrinology and Endocrine Surgery, 2012)
Literature review presents current data on the physiological role of growth factors and their involvement in the formation of benign prostatic hyperplasia and metabolic syndrome.